2020
DOI: 10.3892/ol.2020.11655
|View full text |Cite
|
Sign up to set email alerts
|

Blood cell parameters as prognostic predictors of disease development for patients with advanced non‑small cell lung cancer

Abstract: Although the prognostic value of the neutrophil/lymphocyte ratio (NLR), platelet/lymphocyte ratio (PLR) and lymphocyte/white blood cell ratio (LWR) has been described in advanced non-small cell lung cancer (NSCLC), the association between complete blood cell parameters prior to disease treatment and NSCLC have yet to be identified. The aim of the present study was to assess the complete blood cell parameters prior to disease treatment in patients with advanced NSCLC. A total of 268 patients with advanced NSCLC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 41 publications
1
8
0
1
Order By: Relevance
“…Investigations on other cancers con rmed that the lymphocyte to white blood cell ratio (LWR) is associated with an inferior prognosis in many malignancies, such as nasopharyngeal carcinoma, colorectal carcinoma, and lung cancer. [11][12][13] In our previous study, we also con rmed that low preoperative LWR (< 30%) contributed to a high incidence of recurrence for HCC patients after liver transplantation. 14 However, whether LWR can predict the outcomes of patients with HCC after surgical resection is unclear.…”
Section: Introductionsupporting
confidence: 56%
“…Investigations on other cancers con rmed that the lymphocyte to white blood cell ratio (LWR) is associated with an inferior prognosis in many malignancies, such as nasopharyngeal carcinoma, colorectal carcinoma, and lung cancer. [11][12][13] In our previous study, we also con rmed that low preoperative LWR (< 30%) contributed to a high incidence of recurrence for HCC patients after liver transplantation. 14 However, whether LWR can predict the outcomes of patients with HCC after surgical resection is unclear.…”
Section: Introductionsupporting
confidence: 56%
“…5 In contrast, lymphocytes display completely different behavior and are believed to have anticancer activity; indeed, lymphocytosis itself is considered a favorable prognostic factor. 9 These abnormalities demonstrate a mutual relationship, as reflected in the PLR and NLR parameters. 5,9 Although 7798 their prognostic role of these parameters in NSCLC has been widely discussed in meta-analyses, the authors recommend caution in their interpretation and use in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…9 These abnormalities demonstrate a mutual relationship, as reflected in the PLR and NLR parameters. 5,9 Although 7798 their prognostic role of these parameters in NSCLC has been widely discussed in meta-analyses, the authors recommend caution in their interpretation and use in clinical practice. 10,11 Nevertheless, as the test is widely available and easy to perform, and the results are obtained quickly afterwards, it was included in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our subtype specific NLR ratio cut offs are within similar ranges from these studies, with these reported NLR cut off ratios ranging from between 1.26 to 2.74 [ 6 , 10 , 12 , 15 ]. The range of cut offs reported is likely indicative of intrinsic differences in the cohorts (such as age, menopause status, geographical location, ethnicity), in line with other differences associated with changes in breast cancer outcomes [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 89%